2016
DOI: 10.1126/science.aad5725
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal genome editing partially restores dystrophin expression in a mouse model of muscular dystrophy

Abstract: CRISPR/Cas9-mediated genome editing holds clinical potential for treating genetic diseases, such as Duchenne muscular dystrophy (DMD), which is caused by mutations in the dystrophin gene. To correct DMD by skipping mutant dystrophin exons in postnatal muscle tissue in vivo, we used adeno-associated virus–9 (AAV9) to deliver gene-editing components to postnatal mdx mice, a model of DMD. Different modes of AAV9 delivery were systematically tested, including intraperitoneal at postnatal day 1 (P1), intramuscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
716
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 847 publications
(740 citation statements)
references
References 31 publications
11
716
1
12
Order By: Relevance
“…It is widely used in mammalian genomic editing, including repressing gene expression 1, gene knock‐in 2, repairing disease‐related genes 3 and development of animal models of cancer 4. Increasing evidence suggests that CRISPR/Cas9 may play an important role as a tool in gene therapy for human genetic diseases 5, 6, 7, particularly with recent investigation of pathogenic gene editing in animals 8, 9, 10. Technically, a guide RNA is designed to recognize the target DNA sequence and the Cas9 enzyme induces a double‐stranded break on the DNA of interest.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in mammalian genomic editing, including repressing gene expression 1, gene knock‐in 2, repairing disease‐related genes 3 and development of animal models of cancer 4. Increasing evidence suggests that CRISPR/Cas9 may play an important role as a tool in gene therapy for human genetic diseases 5, 6, 7, particularly with recent investigation of pathogenic gene editing in animals 8, 9, 10. Technically, a guide RNA is designed to recognize the target DNA sequence and the Cas9 enzyme induces a double‐stranded break on the DNA of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The versatility of CRISPR/Cas9‐based platforms makes them promising tools for the correction of monogenetic diseases 23. In 2016, local and systemic delivery of Cas9 and gRNAs with AAV vectors was shown in the mdx mouse, the most frequently used DMD animal model, leading to expression of a truncated but functional dystrophin protein in skeletal and cardiac muscle 24, 25, 26. Young et al 27.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Recently, important progresses have been made in the gene therapy potentials of CRISPR-Cas9. Three studies [10][11][12] simultaneously published in Science reported the ability of CRISPR-Cas9 for in vivo gene therapy when delivered locally (intra-muscular) or systemically (intra-peritoneal or intravenous) into adult or neonatal mice with Duchenne muscular dystrophy (DMD), a disease model caused by a nonsense mutation in exon 23 of Dmd gene. CRISPR-Cas9 targeting intron 22 and intron 23 of Dmd gene can remove the culprit mutation in part of muscle cells and partially restore muscle functions (Figure 1b).…”
mentioning
confidence: 99%
“…CRISPR-Cas9 targeting intron 22 and intron 23 of Dmd gene can remove the culprit mutation in part of muscle cells and partially restore muscle functions (Figure 1b). In these three studies, [10][11][12] CRISPR-Cas9 components were delivered through adeno-associated virus vectors (AAV8 or AAV9), which are preferred delivery tools in gene therapy for their broad tissue tropism, low immunogenicity and minimal insertional mutagenicity. 13 To address the package size limitation of AAV vectors, two studies 10-11 used Cas9 from Staphylococcus aureus (SaCas9) instead of the commonly used Cas9 from Streptococcus pyogenes (SpCas9) because of the smaller size of the former, whereas the third study 12 used spCas9 with a short promoter/enhancer sequence to reduce the package size.…”
mentioning
confidence: 99%
See 1 more Smart Citation